2004
DOI: 10.4064/fm183-2-4
|View full text |Cite
|
Sign up to set email alerts
|

On localizations of torsion abelian groups

Abstract: Abstract. As is well known, torsion abelian groups are not preserved by localization functors. However, Libman proved that the cardinality of LT is bounded by |T | ℵ 0 whenever T is torsion abelian and L is a localization functor. In this paper we study localizations of torsion abelian groups and investigate new examples. In particular we prove that the structure of LT is determined by the structure of the localization of the primary components of T in many cases. Furthermore, we completely characterize the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…We believe that the answer to Farjoun's question is negative as well in the category of abelian groups. It is tempting to use the inclusion n Z/p n ֒→ n Z/p n , which is a localization by [21,Example 6.5], but we have not found an adequate cellularization functor to continue.…”
Section: Cellularizing One Step Furthermentioning
confidence: 93%
“…We believe that the answer to Farjoun's question is negative as well in the category of abelian groups. It is tempting to use the inclusion n Z/p n ֒→ n Z/p n , which is a localization by [21,Example 6.5], but we have not found an adequate cellularization functor to continue.…”
Section: Cellularizing One Step Furthermentioning
confidence: 93%
“…Orthogonality, f -local objects, and f -equivalences have appeared in category theory; then they began to be considered for groups and modules (see [17,18,41,47]). Localization functors have a long history, and the functors were intensively studied in many fields of mathematics.…”
Section: Is a Localization If And Only If The S-module A ⊗ S R Is An mentioning
confidence: 99%
“…Following [47], we partition all idempotent functors to the following four classes. The class I consists of all functors L such that LZ(p ∞ ) = Z(p ∞ ).…”
Section: Corollary 112 Ifmentioning
confidence: 99%
“…[2,4], or [8]. See [10] for localizations of torsion abelian groups. In [4] it was shown that localizations of torsion-free abelian groups exist in abundance.…”
Section: Introductionmentioning
confidence: 98%